ANALISIS KEPUASAN PENGGUNA MARKETPLACE PADA APLIKASI FACEBOOK MENGGUNAKAN METODE DELONE AND MCLEAN - Putri Nawang Wulan; Kurniabudi Kurniabudi; Imam Rofi’i (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
Trading in the modern era currently uses a buying and selling system, not directly face to face but only with one finger and in one place, not limited by space and time, which is commonly referred to as buying and selling online and online transactions in one container, namely the website and very there are many types of marketplaces as long as technology continues to develop and changes in the quality of technology continue, in this study the author wants to analyze the Facebook Marketplace with the Delone and McLean method, which has problems such as vulgar advertisements that can be accessed by minors, the sale of goods-prohibited items and there are still many users who violate the rules and conditions set by the Facebook Marketplace. The purpose of this study is to identify and analyze these problems and also to find out which factors have the most influence on user satisfaction with the Facebook Marketplace. Based on the results of processing questionnaire data from the people of Jambi City, it was found that 4 of the 9 hypotheses that had a positive and significant effect were service quality to users, use to user satisfaction, use to net benefits and user satisfaction to net benefits.